PERBANDINGAN USIA MENARKE DAERAH PEDESAAN DAN PERKOTAAN DI TANGERANG - , dr. Dewi Darmawati; , Prof. dr. Sunartini H., Ph.D, Sp AK ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The transition stage of physical and sexual maturation to become an adult form is an adolecent or adolescence period. The transition of physical and sexual developments are moving in the same time as the development of cognitive, emotional, social cultural and adaptation ability. Girl puberty or sexual maturity is marked by the first menstruation or menarche. The link between menarche and height growth spurt is very close, menarche in girls occurs when the rate began to decline in height growth, menarche is the most important phase of reproductive development. Many factors influence the onset of menarche ie: physical activity, nutrition, socio economic, environmental conditions and access to medical services. These factors are variable within area. Girls in urban area tend to have sedentary life style compare with its counterpart. The purpose of this study is to compare the onset of menarche in urban and rural area, and to identify factors that influenced the differences. We conducted a cross sectional study in Tangerang, Banten. Obtained sample are 220 elementary school girls from both urban and rural area who have entered the inclusion criteria. The mean age of menarche all study subjects was 11.46 ± 0.99 years, while the average age of menarche girls who live in rural area slower than girls who live in urban area (11.87 ± 0.99 vs 11.05 ± 0.80 p=0.01). Birth weight, body length of birth, physical activity and environment condition were significantly influence the onset of menarche. The girls who live in urban area have an earlier predictor factor to achieve for onset of menarche than those live in rural area (OR: 3.34 [95% CI: 1.911 to 5.823] and aOR: 2.95 [95% CI: 1.410 - 6.012]).